Використання ортогонально-поляризованих шумоподібних радіосигналів для придушення сигналів управління та навігації БПЛА - Білик, О. С. (ХНУРЕ, 2024)
This report presents a detailed analysis of using orthogonally-polarized noise-like radio signals for effectively jamming the radio-frequency signals that control Unmanned Aerial Vehicles (UAVs). These signals, characterized by a broad frequency spectrum, are difficult to detect and suppress. Orthogonal polarization allows targeted impact on UAV receiving antennas regardless of their orientation, disrupting UAV-operator communication, stabilization, satellite links, and video data transmission. The report discusses the adaptability of Electronic Warfare (EW) systems to different UAV types and control methods, highlighting the use of Software Defined Radio (SDR) technology.
Keywords: шумоподібнй радіосигнал; навігація БПЛА